Ekonomi-Politik Kebijakan Impor Garam Indonesia Periode 2007-2012 - Lukman Baihaki (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
Indonesia currently has salt importation policy. This policy is result of various interests between Ministry of Trade, Ministry of Industry, Ministry of Marine Affairs and Fisheries, PT. Cheetham Garam Indonesia and Indonesian Association of Salt Harvesters. In this struggle of interests, both Ministry of Trades and Ministry of Industries support PT. Cheetham Garam Indonesia as the Indonesian most influential salt importir. In the other hand, Indonesian Association of Salt Harvesters is supported by Ministry of Marine Affairs and Fisheries. Indonesian current policy prefers to support salt importation overseas instead of trying to increase national salt harvesters’ productivity. This tendency affect Indonesia’s dependency on salt importation.